Utilization of Nanochitosan as Adsorbent of Mercury (Hg) in Gold Ore Processing Waste - Nadhifa Aliyya Himawan; Handoko Darmokoesoemo; Totok Ardiarto; A. Budi Prasetya; Badrud Tamam Ibnu Ali (Eksergi, 2022)
Mercury pollution in gold ore processing wastewater can cause environmental and health problems. A large amount of mercury pollution causes neurological disease, paralysis, loss of sense of taste, irregular speech, and death. One effective method to reduce mercury amount in the environment is adsorption. Adsorption performance is affected by several factors such as surface area of material, deacetylation degree (DD), and adsorption condition, which is indicated by contact time and mercury concentration. Nanochitosan is used in this research. Effect of deacetylation degree (85%; 87%; 95%), contact time (30;60;90;120 minutes), and variation of mercury concentration (5;10;15;20;25;30 ppm) on adsorption performance was investigated in this research. Nanochitosan in this research is characterized by FTIR, SEM-EDX, BET-BJH, and pH PZC. AAS measures adsorption performance in this research. The result shows that nanochitosan, which has the best adsorption performance, is nanochitosan with a deacetylation degree of 95%, at a contact time of 60 minutes, and mercury concentration is 15 ppm.